Endometriosis, Angiogenesis and Tissue Factor - Graciela Krikun (Scientifica)
Tissue factor (TF), is a cellular receptor that binds the factor VII/VIIa to initiate the blood coagulation cascade. In addition to its role as the initiator of the hemostatic cascade, TF is known to be involved in angiogenesis via intracellular signaling that utilizes the protease activated receptor-2 (PAR-2). We now review the physiologic expression of TF in the endometrium and its altered expression in multiple cell types derived from eutopic and ectopic endometrium from women with endometriosis compared with normal endometrium. Our findings suggest that TF might be an ideal target for therapeutic intervention in endometriosis. We have employed a novel immunoconjugate molecule known as Icon and were able to eradicate endometrial lesions in a mouse model of endometriosis without affecting fertility. These findings have major implications for potential treatment in humans.